PRIESTS, TECHNICIANS AND TRADERS? THE DISCURSIVE POLITICS OF BRAZIL’S AGRICULTURAL COOPERATION IN MOZAMBIQUE/ Sacerdotes, técnicos e investidores? A política discursiva da cooperação agrícola brasileira em Moçambique/¿Sacerdotes, técnicos e inversores? La política discursiva de la cooperación agrícola de Brasil en Mozambique - Cabral, Lidia (REVISTA NERA, 2017)
This paper is situated in an emerging body on Brazilian development cooperation, looking at the specific case of cooperation concerning agricultural development in Africa. The analysis highlights the discursive side of Brazilian cooperation, where competing narratives about models and purposes construct different versions of reality for reasons related to the political character of cooperation. Discourse is hence an expression of the political. This paper frames Brazil’s agricultural cooperation as a domain of priests, technicians and traders, driven, respectively, by doctrinal, technical fixing and business rationales. This provides an initial frame of reference to distil actors’ narratives about Brazilian cooperation programmes. The paper focuses on two cooperation programmes in Mozambique: ProSAVANA and More Food International. The key for understanding competing narratives on these programmes and how they intermingle and change over time can be found in Brazil’s domestic sphere. The two programmes have been interpreted as an expression of contradictions in Brazil’s agriculture and particularly its dualistic character, typically framed as family farming versus agribusiness. Through the lenses of discourse analysis, this paper offers a critical reading of the interplay between priests, technicians and traders, as shaped by different interests and points of view in cooperation relations.